PELABELAN ETNIS MINANGKABAU PADA WANITA PELAKU PENYIMPANGAN SOSIAL DI KOTA PADANG - Erianjoni Erianjoni (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The article describes the forms of labels provided by the public in the city of Padang as part of Minangkabau culture, particularly aimed at women who pass social deviation in behavior related to the community. Labeling Minangkabau society has a sociological and anthropological meaning, which is actually aimed at social control or awareness deviant actors, namely the Minangkabau woman who occupies an important position in a matrilineal society. Keywords: Labeling Minangkabau ethnic, women, social deviationCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i1.92